Investigation of the Effect of Cutting Parameters on Surface Roughness by a New Type of Plane Surface Grinding Mechanism (YTM) - Adiyaman, Oktay; Savas, Vedat (Gazi Univ, 2017)
The new plane surface grinding mechanism (YTM) is a new plane surface grinding mechanism obtained with the mechanism developed. In the traditional plane surface grinding mechanism, the wheel has only a single rotation. The wheel rotates circumferentially around its axis. In YTM, on the other hand, there are two rotations. The first rotation is the same with the traditional grinding mechanism, which is the circumferential rotation. The other rotation is the newly developed axial rotation, where the wheel rotates around itself perpendicular to its radial axis. This totational is called axial rotation. Thus, the wheel has two rotations. Experiments were made for this newly developed method using various parameters and surface raughness (Ra) values were measured. Five wheels with different kinds were chosen. Workpieces were grinded with all these different combinations and effects on surface roughness were investigated. As a result, YTM produced smaller surface roughness values than the traditional method. Surface roughness values were very close in every part of grinded work pieces. YTM is also very low in cost and can be adapted to all milling machines and CNC machines. It can be safely said that YTM is better than the traditional system because of all these directions.
Keywords: Grinding mechanism; plane surface grinding; surface roughness; grinding parameters